Public perception of biofuel usage in Sarawak - Susalia Mapong, Sabarang (Universiti Malaysia Sarawak (UNIMAS), 2020)
Biofuels are a source of recycled or waste renewable energy that can help reduce carbon dioxide emissions. Biofuels are one of today 's largest renewable energy sources. Biofuel technology is capable of reducing greenhouse gas emissions and for the usage of fossil fuels. Sarawak is one of the region's strongest supporters to push for the transportation system to include biofuels. Unfortunately, it is still far from successful because the biofuel among people in Sarawak has not really noticed. Therefore, here will report the public perception of biofuel usage in Sarawak in terms of consumer attitudes strength, environmental knowledge, social influence and perceived behavioural control. The results of this study divulge that positive significant effects of environmental concern upon consumer attitudes strength towards public perception of biofuel. As for the environmental knowledge, there is a positive relationship with public perception of biofuel usage. However, social influence and perceived behavioural control did not show the significant to the public perception towards biofuel. From the result, Sarawak citizens frequently making choices based on their current situation, with the exception that they were more positive toward the environmental and renewable aspects of biofuel use. More research recommendations include an improved understanding of the potential positive influences that affect public perceptions of biofuels.